Receiver design in multicarrier direct-sequence CDMA communications. - Hui Liu
Multicarrier direct-sequence code-division multiple access (MC-DS-CDMA) has emerged recently as a promising candidate for the next generation broad-band mobile networks. We consider the design of multiuser receivers for MC-DS-CDMA communications over fading channels. We present a class of spreading codes that enables the simple despreading-combining receiver to achieve the performance of the optimum multiuser linear receiver. These codes are shown to be optimum for independent fading channels under a code design criterion derived. Also derived are analytic solutions of optimum spreading codes for any given channel fading statistics. Simulation results are provided to demonstrate the significant gains in performance and simplicity due to the proposed techniques
Keywords: MC-DS-CDMA communications; Analytic solutions; Broadband mobile networks; Channel fading statistics; Code design; Code-division multiple access; Despreading-combining receiver; Fading channels; Independent fading channels; Multicarrier DS-CDMA communications; Multiuser receivers; Optimum multiuser linear receiver; Optimum spreading codes; Receiver design; Simulation results